A feasibility study of implementation of oxy-fuel combustion on a practical diesel engine at the economical oxygen-fuel ratios by computer simulation. (December 2020) - Li, Xiang; Peng, Zhijun; Ajmal, Tahmina; Aitouche, Abdel; Mobasheri, Raouf; Pei, Yiqiang; Gao, Bo; Wellers, Matthias
To help achieve zero carbon emissions from inland waterway vessels, this implementation of oxy-fuel combustion on a practical diesel engine at the economical oxygen-fuel ratios were systematically studied and analysed in this paper. A 1-D simulation was used to explore the effect of various operating parameters for recovering the engine power when the engine is modified to the oxy-fuel combustion from conventional air combustion. The brake power of oxy-fuel combustion is only 26.7 kW that has a noticeable decline compared with 40 kW of conventional air combustion with fixed consumption of fuel and oxygen. By optimising some valuable parameters, like fuel injection timing, intake charge temperature, intake components, engine compression ratio and water injection strategy, a benefit of 6.8 kW has been acquired in the engine power. Afterwards, a remarkable benefit was obtained with the increase of lambdaO2 from 1.0 to 1.5, finally obtaining the same engine power with the conventional air combustion. Above all, taking advantage of various operating parameters, it is expected to further improve the value of the implement of oxy-fuel combustion on diesel engines at the economical oxygen-fuel ratios.